Understanding intercultural virtual exchange through a translanguaging lens in Chinese as a foreign language - Guo Zhiyan; Xu Xinyue (Journal of China Computer-Assisted Language Learning)
Virtual exchange refers to technology-enabled online communication between people who are geographically separated from each other. It has been increasingly adopted in education in the past two decades, especially since early 2020 when teachers and students were forced to move to an online mode of teaching and international exchange owing to the most recent pandemic. The current study is based on a nine-week virtual exchange project that took place between 22 students learning Chinese as a foreign language (CFL) from a British university and their partners from a Chinese university. The subjects conversed online with each other on self-directed topics on a weekly basis, and they completed their collaboration project for showcasing in the final week. From a translanguaging perspective, naturally occurring online conversations between intercultural interlocutors were investigated through the method of multimodal conversation analysis (MCA). The students leveraged a range of linguistic, semiotic and multimodal resources to navigate through communication with their partners. It is hoped that this study will contribute to the understanding of how translanguaging is embodied in virtual exchange interaction and how MCA can be applied to reveal the details present at the micro level of intercultural exchanges in the CFL context.